Safety of the Wearable Cardioverter Defibrillator (WCD) in Patients with Implanted Pacemakers. Issue 3 (8th February 2017) - SCHMITT, JOERN; ABACI, GUEZINE; JOHNSON, VICTORIA; ERKAPIC, DAMIR; GEMEIN, CHRISTOPHER; CHASAN, RITVAN; WEIPERT, KAY; HAMM, CHRISTIAN W.; KLEIN, HELMUT U.
Abstract : Background: The wearable cardioverter defibrillator (WCD) is an important approach for better risk stratification, applied to patients considered to be at high risk of sudden arrhythmic death. Patients with implanted pacemakers may also become candidates for use of the WCD. However, there is a potential risk that pacemaker signals may mislead the WCD detection algorithm and cause inappropriate WCD shock delivery. The aim of the study was to test the impact of different types of pacing, various right ventricular (RV) lead positions, and pacing modes for potential misleading of the WCD detection algorithm. Methods: Sixty patients with implanted pacemakers received the WCD for a short time and each pacing mode (AAI, VVI, and DDD) was tested for at least 30 seconds in unipolar and bipolar pacing configuration. In case of triggering the WCD detection algorithm and starting the sequence of arrhythmia alarms, shock delivery was prevented by pushing of the response buttons. Results: In six of 60 patients (10%), continuous unipolar pacing in DDD mode triggered the WCD detection algorithm. In no patient, triggering occurred with bipolar DDD pacing, unipolar and bipolar AAI, and VVI pacing. Triggering was independent of pacing amplitude, RV pacing lead position, and pulse generator implantation site. Conclusion: Unipolar DDD pacing bears a high risk of false triggering of the WCD detection algorithm. Other types of unipolar pacing and all bipolar pacing modes do not seem to mislead the WCD detection algorithm. Therefore, patients with no reprogrammable unipolar DDD pacing should not become candidates for the WCD.